EFFECT OF SALICYLIC ACID SPRAYING ON YIELD AND IT’S COMPONENTS OF LINSEED CULTIVARS - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A field trails was carried out during winter season of 2017-2018 and 2018-2019 at Field Crops Department - College of Agricultural Engineering Sciences - University of Baghdad / Jadriyah to study the effect of salicylic acid spraying on yield and it’s components of linseed cultivars. Randomized complete block design (RCBD) arranged within split plots was used with three replicates. The trail included three salicylic acid concentrations (100, 200 and 300 mg L-1) in addition to control treatment (distilled water spraying) within main plots and three linseed cultivars (Syrian, Egyptian and Iraqi local) within sub plots. The results showed that the Syrian cv. produced the highest number of main branches 7.09 and 7.11 branch plant-1, sub branch 28.45 and 27.10 branch plant-1 and number of capsules 122.39 and 117.89 capsule plant-1, number of seeds 8.63 and 8.45 seed capsule-1, seed yield 1.19 and 1.17 mton ha-1, while the Egyptian cv. gave highest means of 1000 seeds weight 6.83 and 6.54 g for the two seasons, respectively. The results showed that the spraying of salicylic acid at 200 mg L-1 significantly superiored and produced the highest number of main branches 7.10 and 6.82 branch plant-1, sub branch 29.05 and 26.48 branch plant-1, number of capsules 120.48 and 114.54 capsule plant-1, number of seeds 8.44 and 8.26 seed capsule-1 and seed yield 1.19 and 1.15 mton ha-1, for the two seasons, respectively. The interaction between the two factors had significant effect on all studied characters.